2017
DOI: 10.1002/cncr.30704
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and outcomes of older patients with secondary acute myeloid leukemia according to treatment approach

Abstract: BACKGROUND Developing newer strategies to improve outcomes in older patients with secondary AML is a critical unmet need. Establishing baseline metrics from which to evaluate newer approaches is important. METHODS Secondary AML was defined by one or more of the following: history of antecedent hematological disorder; the diagnosis of therapy related AML; AML with karyotype abnormalities characteristic of MDS. Newly diagnosed secondary AML (s-AML) patients aged 60–75 years were grouped into 5 treatment cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
56
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 53 publications
4
56
1
Order By: Relevance
“…Consistent with previous studies, we observed that both e‐AML and s‐AML were associated with lower CR rate and a short duration of EFS and OS. Although some new therapeutic agents were applied to these high‐risk AML patients, the treatment of e/s‐AML remains a challenge, and there is no consensus on this controversial issue.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with previous studies, we observed that both e‐AML and s‐AML were associated with lower CR rate and a short duration of EFS and OS. Although some new therapeutic agents were applied to these high‐risk AML patients, the treatment of e/s‐AML remains a challenge, and there is no consensus on this controversial issue.…”
Section: Discussionsupporting
confidence: 92%
“…Until recently, therapeutic strategies did not really differ from de novo AML. Patients are offered induction chemotherapy and allogeneic stem‐cell transplantation if deemed fit for intensive therapies, those considered unfit for such treatment receive hypomethylating agents (HMA), low dose cytarabine or supportive care …”
Section: Introductionmentioning
confidence: 99%
“…Patients are offered induction chemotherapy and allogeneic stem-cell transplantation if deemed fit for intensive therapies, those considered unfit for such treatment receive hypomethylating agents (HMA), low dose cytarabine or supportive care. 3,4,7 The CPX-351 trial has been specifically designed for older patients with secondary or high-risk AML and demonstrated the superiority of the dual-drug liposomal encapsulation of daunorubicin and cytarabine (CPX-351) over the conventional "7 + 3" cytarabine-daunorubicin regimen. 8 This phase 3 study represents a unique example of prospective data in this rare AML subgroup providing a solid basis for comparison with real life data.…”
Section: Introductionmentioning
confidence: 99%
“…The main risk factor for the development of AML is increasing age, and although there rarely are other identifiable predisposing factors, there is an increasing number of AML cases after exposure to chemotherapy or radiotherapy (collectively referred to as “therapy‐related AML” [t‐AML]). There also is a distinct high‐risk category of secondary AML (s‐AML) after antecedent hematological disorders, such as myelodysplastic syndromes (MDS) or myeloproliferative neoplasms . Outcomes of AML in older adults (aged >60 years) are dismal, with survival rates reported to be <10% at 3 years and <5% at 5 years .…”
Section: Introductionmentioning
confidence: 99%
“…There also is a distinct highrisk category of secondary AML (s-AML) after antecedent hematological disorders, such as myelodysplastic syndromes (MDS) or myeloproliferative neoplasms. 2 Outcomes of AML in older adults (aged >60 years) are dismal, with survival rates reported to be <10% at 3 years and <5% at 5 years. 3,4 Therapeutic challenges include both a more aggressive biology of the disease as well as a patient that is more susceptible to the toxic effects of chemotherapy.…”
Section: Introductionmentioning
confidence: 99%